2020
DOI: 10.1186/s12981-020-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIV drug resistance profiles across HIV-1 subtypes A and D for patients receiving a tenofovir-based and zidovudine-based first line regimens in Uganda

Abstract: Background: Resistance to antiretroviral drugs is a major challenge among Human Immunodeficiency Virus (HIV) positive patients receiving antiretroviral therapy (ART). Mutations that arise as a result of this are diverse across the various drugs, drug classes, drug regimens and subtypes. In Uganda, there is a paucity of information on how these mutations differ among the different drug regimens and the predominant HIV-1 subtypes. The purpose of this study was to determine mutation profile differences between fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Strikingly, in our nationwide work in Brazil we found that K65R was the only SDRM that followed an accentuated increase in prevalence over the studied years (2.23% in 2008 to 12.11% in 2017). The increasing and preferential usage of TDF in the clinical practice [ 21 ], including in a context of a failing regimen, could be the primordial reason for the significant expansion of K65R as other studies show a higher prevalence of this mutation in patients failing ART treatment [ 15 , 52 , 53 , 54 , 55 ]. However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, in our nationwide work in Brazil we found that K65R was the only SDRM that followed an accentuated increase in prevalence over the studied years (2.23% in 2008 to 12.11% in 2017). The increasing and preferential usage of TDF in the clinical practice [ 21 ], including in a context of a failing regimen, could be the primordial reason for the significant expansion of K65R as other studies show a higher prevalence of this mutation in patients failing ART treatment [ 15 , 52 , 53 , 54 , 55 ]. However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…When this group was analyzed for crossresistance to the other NNRTIs, only 25.2% (n=36) were susceptible to etravirine and rilpivirine and 15.4% (n=22) were susceptible to doravirine. 22…”
Section: Emerging Literature and Discussion Resistancementioning
confidence: 99%
“…Reduced viral sensitivity to zidovudine largely results from an accumulation of mutations, with a mutation at codon 70 (K70R) emerging first, followed by codon 215 substitutions (T215Y or T215F) and mutations at codon 41(M41L) [ 71 , 72 ]. The combination of mutations 215 and 41 confers the highest level of zidovudine resistance.…”
Section: Nrti Drug Resistancementioning
confidence: 99%